2016
DOI: 10.1107/s2059798315021671
|View full text |Cite
|
Sign up to set email alerts
|

Structure ofD-alanine-D-alanine ligase fromYersinia pestis: nucleotide phosphate recognition by the serine loop

Abstract: D-Alanyl-D-alanine is an essential precursor of bacterial peptidoglycan and is synthesized by D-alanine-D-alanine ligase (DDL) with hydrolysis of ATP; this reaction makes DDL an important drug target for the development of antibacterial agents. Five crystal structures of DDL from Yersinia pestis (YpDDL) were determined at 1.7-2.5 Å resolution: apo, AMP-bound, ADP-bound, adenosine 5'-(β,γ-imido)triphosphate-bound, and D-alanyl-D-alanine- and ADP-bound structures. YpDDL consists of three domains, in which four l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…43 Sequence Analysis. The sequence of AhDdl was aligned with D-alanine−D-alanine ligase sequences from Thermus caldophilus (TcDdl, 33.90%), 44 Staphylococcus aureus COL (SaDdl, 32.29%), 20 Thermus thermophilus HB8 (TtDdl, 33.91%), 45 Yersinia pestis (YpDdl, 32.21%), 46 and Mycobacterium tuberculosis (MtDdl, 36.22%) 15 (Figure 4). The identity ranged from 32.21% identity for YpDdl to 36.22% identity for MtDdl; nevertheless, the structure-based sequence alignments of AhDdl, TcDdl, SaDdl, TtDdl, YpDdl, and MtDdl showed that the active sites were conserved in the Ddls (Figure 4) and the lengths of loop 1 (Gly13-His17), loop 2 (Ala162-Ser167), and loop 4 (Phe297-Met305) were the same.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Sequence Analysis. The sequence of AhDdl was aligned with D-alanine−D-alanine ligase sequences from Thermus caldophilus (TcDdl, 33.90%), 44 Staphylococcus aureus COL (SaDdl, 32.29%), 20 Thermus thermophilus HB8 (TtDdl, 33.91%), 45 Yersinia pestis (YpDdl, 32.21%), 46 and Mycobacterium tuberculosis (MtDdl, 36.22%) 15 (Figure 4). The identity ranged from 32.21% identity for YpDdl to 36.22% identity for MtDdl; nevertheless, the structure-based sequence alignments of AhDdl, TcDdl, SaDdl, TtDdl, YpDdl, and MtDdl showed that the active sites were conserved in the Ddls (Figure 4) and the lengths of loop 1 (Gly13-His17), loop 2 (Ala162-Ser167), and loop 4 (Phe297-Met305) were the same.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The asymmetric unit with P2 1 2 1 2 1 symmetry contained two subunits arranged as a face-to-face homodimer, which was mainly maintained by three helices (α2, α3, and α4). Like other Ddls (TcDdl, PDB ID: 2FB9; 44 SaDdl, PDB ID: 2I80; 20 TtDdl, PDB ID: 2ZDG, 2ZDH, 2ZDQ; 45 YpDdl, PDB ID: 4ZQI 46 and MtDdl, PDB ID: 3LWB 15 ), each subunit of AhDdl was composed of three distinct domains, an Nterminal domain (domain 1, Met1-Asp106), a central domain (domain 2, Ala107-Gly200), and a C-terminal domain (domain 3, Pro201-Val329) (Figure 5A,B). Data collection and refinement statistics are summarized in Table 1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The open reading frame sequence encoding ToCDS protein from Thermococcus onnurineus NA1 was amplified by PCR using the genomic DNA isolated from Thermococcus onnurineus NA1 as a template according to a previously described method [19]. The sequences of the oligonucleotide primers were designed based on the data on genome sequences of Thermococcus onnurineus NA1 from the NCBI website.…”
Section: Methodsmentioning
confidence: 99%
“…Ddl involved in peptidoglycan precursor biosynthesis is expressed by the ddl gene and is widely distributed in Gram‐positive and Gram‐negative bacteria (Albar et al., 1992; Tran et al., 2016). It has two isoenzymes, D‐alanine‐D‐alanine ligase A (DdlA) and D‐alanine‐D‐alanine ligase B (DdlB; Batson et al., 2010), which display similar kinetic characteristics, substrate specificity, and sensitivity to known Ddl inhibitors (Daub et al., 1988; Fan et al., 1997; Zawadzke et al., 1991).…”
Section: Structure and Function Of Ddlmentioning
confidence: 99%